GLOBALISASI PERBANKAN SYARIAH: TINJAUAN TEORITIS DAN PRAKTIS DALAM MENGHADAPI MASYARAKAT EKONOMI ASEAN 2015 - Hayat Hayat (State Institute of Islamic Studies (IAIN) Palu, 2014)
The thought modern society towards banking system has undergone various changes so that their textual perspective to the banking law becomes negative. The Syariah banking has undergone a variety of dynamics. Challenge to the competition to improve the quality of service continues to conduct by giving various ease, usefulness, usability, kindness, and to make a law that does not violate any of the laws of Islam, became a necessity. Modern society should no longer view the symbol highlighted by the banks, but rather the aspect of their service, the benefits gained , the security of service value, and the ease obtained. In order to be accepted by the whole modern society. the Islamic banking should no longer consider the background of its customer-to be, and must develop the service required by customers, instead.Kata Kunci: transformasi, perbankan Islam, Ekonomi Islami